EFFECT OF WATER HYACINTH BOKASHI FERTILIZER AND NPK 15-15-15 FERTILIZER APPLICATION ON GROWTH AND YIELD OF PARIA (Momordica charantia L) - Nur Fadillah Hutahayan; Cik Zulia; Safruddin Safruddin (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was conducted on the research garden of Faculty of Agriculture University of Asahan, Kisaran Naga Village, Kisaran Timur Subdistrict, Asahan District in March to May 2017. The experiment was arranged in Randomized Complete Block Design with two factors and 3 replication. The first factor is four concentrate of water hyacinth bokashi fertilizer with B0 = 0 kg/plot, B1 = 1,08 kg/plot, B2 = 30 2,16 kg/plot, B3 = 3,24 kg/plot, while the second factor is theNPK 15-15-15 fertilizer with three levels is N0 = 0 g/plot, N1 = 25,31 g/plot, N2 = 50,63 g/plot. Parameters were observed: plant length, number of leaf, yield per plant and yield per plot. The analysis statistic showed that water hyacinth bokashi fertilizer and NPK 15-15-15 fertilizer traetment have significantly effect on the all parameters. The best effect showed with B2 treatment that on the parameter of plant length have 23,86 cm, the number of leaf have 10.52seet, the yield per plant have 2,41 kg and yield per plot have 7,50 kg. While the NPK 15-15-15 fertilizer treatment give the best effect with N1 treatment on the parameter of plant length have 26,13 cm, yield per plant have 2,64 kg and yield per plot have 8,02 kg.